Synthesis of 1,2,3-Triazole-Linked Glycoconjugates of N-(2-Aminoethyl)glycine: Building Blocks for the Construction of Combinatorial Glycopeptide Libraries - Günther, Kai Uwe; Ziegler, Thomas (Synthesis, 2014)
Twenty-nine glycoconjugate building blocks based on the N-(2-aminoethyl)glycine (AEG) backbone and sugars linked to the backbone by a 1,2,3-triazole moiety were prepared via copper-catalyzed 1,3-dipolar cycloaddition of monosaccharides bearing an azide group and N-4-pentynoyl-AEG. The initial glycoconjugates were converted to the corresponding acids and pentafluorophenyl esters, respectively, which are useful building blocks for the construction of combinatorial glycopeptide libraries.
Keywords: carbohydrates; glycopeptides; glycoconjugates; amino acids; azides